حاجة سوق العمل فى فلسطین (الضفة الغربیة ) لاخصائى علم المکتبات و المعلومات : دراسة مسحیة تحلیلیة مقارنة مع التخصصات الأخرى فى اعلانات وظائف صحیفة القدس - د. ابراهیم خلیل یوسف خضر (المجلة الدولية لعلوم المكتبات والمعلومات)
The previous seven years have witnessed a remarkable demand for libraries’ science specialists with a slight difference in the extent of this demand according to the economical and political varied situations. The study aimed to identify the job market’s need in Palestine during the previous seven years , and compare it with majors that are intensively demanded, such as : (All branches of engineering , all branches of accounting , and all branches of computer science.) in the era (1/1/2005 - 31/12/2012) through what was announced by (Al Quds Newspaper ) as the bestseller among all Palestinian newspapers ; since it published (2525) publications. Moreover, a survey was conducted in the communities of the West Bank , in order to identify the need for the specialists in that aspect . The study also aimed to answer the following questions:1- What were the job market’s needs in Palestine for libraries’ and information specialists in the previous seven years?2- What are the future needs for employing libraries’ specialists in Palestine(West Bank)?3- In the light of the study’s results, what is the Palestinian market need for opening programs with various academic degrees in libraries and information science to supply it with its need of specialized vocational majors?The Study Importance :The importance of this study steps out of its being the first study in Palestine that discusses the need of the Palestinian market for specialists in libraries and information science as far as the researcher knows , and according to jobs’ announcements that were published in (Al Quds Newspaper) . The study also provides trusted data about the Palestinian job market in the Palestinian Information Sector , in addition to shedding the light on the real situation of the current job market and its requirements of academic programs in the Palestinian universities and colleges , so as to cover the job market’s needs of specialists in the field of libraries and information science . It fruitful to point here that the study found no Palestinian university , institution, or college offers this specialization or program.The Study Aspect:The researcher intended to study the employment vacancies that were advertised in (Al Quds Newspaper) in the previous seven years ( form the beginning of 2005 to the end of 2012) for libraries and information science’s specialists , and the job vacancies for the other majors that are more demanded according to the job market’s need for them in a broad sense. A comprehensive survey for employing organizations in Palestine (for this specialization) was conducted to identify its need and its feasibility for the Palestinian universities and colleges .